Upaya pengembangan motivasi siswa belajar matematika - Afifi, Muhammad Rifkhan; Qotrunnada, Maulida Hasbiya (Maliki Interdisciplinary Journal, 2024)
This journal article aims to investigate the strategies and implementation of developing motivation to learn mathematics among all school students. This research method uses conceptual analysis. This research takes students as its object. And the results of this study show that there are various learning strategies and methods that can be used to increase motivation to learn mathematics. The implementation of these strategies plays a crucial role in creating a learning environment that supports, motivates and inspires students to be more active in the learning process of mathematics. The implications of this research provide valuable insights for educators and policy makers in designing motivating learning programmes in mathematics, so as to improve students’ academic performance and interest in the subject.